2015
DOI: 10.1523/jneurosci.3869-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Movement Preparation Time on the Expression of Visuomotor Learning and Savings

Abstract: Following a change in the environment or motor apparatus, human subjects are able to rapidly compensate their movements to recover accurate performance. This ability to adapt is thought to be achieved through multiple, qualitatively distinct learning processes acting in parallel. It is unclear, however, what the relative contributions of these multiple processes are during learning. In particular, long-term memories in such paradigms have been extensively studied through the phenomenon of savings-faster adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
366
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(418 citation statements)
references
References 56 publications
25
366
5
Order By: Relevance
“…In order to unmask potential habitual selection of the original response, we forced participants to act at different response times, ranging from 0-1200 ms, using a forced-response paradigm 17,23,24 ( Figure 3a). Four tones were played, each separated by 400ms, and participants were instructed that they must make a response synchronously with the final tone.…”
Section: Limiting Reaction Times Revealed Habitual Selection Followinmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to unmask potential habitual selection of the original response, we forced participants to act at different response times, ranging from 0-1200 ms, using a forced-response paradigm 17,23,24 ( Figure 3a). Four tones were played, each separated by 400ms, and participants were instructed that they must make a response synchronously with the final tone.…”
Section: Limiting Reaction Times Revealed Habitual Selection Followinmentioning
confidence: 99%
“…This implies that both mappings were represented during each trial, demonstrating the existence of multiple components of learning. The relative expression of different components of learning has previously been shown to be influenced by limiting cognitive resources 26,27 , including available preparation time 17,20,22,28,29 . However, previous research has manipulated preparation time in a relatively simple 'high-or-low' manner 17,20 , or based on spontaneous variations in 'voluntarily' selected reaction times 29 .…”
Section: Limiting Reaction Times Unmasks Habitual Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, recent work has shown that the pattern of behavior observed in visuomotor savings experiments is often inconsistent with an error-based process, and may be better explained as reflecting changes in action selection that facilitate performance (Huang et al, 2011;Haith et al, 2015;Huberdeau et al, 2015;McDougle et al, 2015;Orban de Xivry and Lefévre, 2015).…”
Section: Introductionmentioning
confidence: 97%